PyTorch 1.x Reinforcement Learning Cookbook : Over 60 recipes to design, develop, and deploy self-learning AI models using Python /: Over 60 recipes to design, develop, and deploy self-learning AI models using Python. (2019) - Liu, Yuxi (Hayden)
No abstract available